Costless and Costly Prosociality: Correspondence Among Personality Traits, Economic Preferences, and Real-World Prosociality. Issue 4 (May 2019) - Ferguson, Eamonn; Zhao, Kun; O'Carroll, Ronan E.; Smillie, Luke D.
Prosociality can either be costly (e.g., donating to charity) or costless (e.g., posthumous organ donation). Whereas links between personality and costly prosociality have been explored, links with costless prosociality and personality are at present unknown. We address this in two studies: Study 1 ( N = 200) confirms the distinction between costless and costly prosociality based on willingness to engage with health and nonhealth prosociality. Study 2, using data from four samples (student and community; N = 733) shows, across incentivized and hypothetical economic games to assess costless (generosity game [GG]) and costly (dictator game [DG]) prosociality, that organ donor behavior was linked to greater allocations in the GG and that charity/volunteering behavior was linked to greater allocations in the DG. Costless and costly prosocialities are associated with different personality traits (e.g., costly with politeness and compassion and costless with intellect). Implications for cooperative phenotypes and recruiting organ donors are discussed.